Blame, responsibility and agency: 'Disaster justice' and the state in the Philippines. (September 2018) - Bankoff, Greg
The notion of 'disaster justice', that is that governments have a responsibility to protect the vulnerable seems premised on a particular conception of the state that conforms to a Western liberal democratic model. Indeed, the failure of the state to protect its own is regarded not only as an injustice but as 'a breach of democracy's fundamental obligation to its citizens'. The state is seen as having a mandatory duty to shield people from physical harm through its laws and policies as well as to manage the social vulnerability consequent upon inequitable social systems. So what happens when societies are not democratic or free (or otherwise 'free') and where the state is premised upon a very different set of criteria? If injustice demands someone to blame, does justice require someone to absolve? By looking closely at the nature of hazards and people's expectations of the state and state actions in one region of southern Luzon around Mt Mayon, one of the most active volcanoes in the Philippines, this paper explores whether and how a sense of responsibility for vulnerable populations developed over time. It takes a comparative perspective through an examination of the colonial and contemporary state periods to discover what relevancy the concept of disaster justice has in different temporal and contextual situations.